Investigation of novel solid lipid microparticles based on homolipids from Bos indicus for the delivery of gentamicin - C. Kenechukwu, Franklin; A. Momoh, Mumuni; C. Umeyor, Emmanuel; M. Uronnachi, Emmanuel; A. Attama, Anthony (International Journal of Pharmaceutical Investigation)
Background: The aim of this study was to formulate solidified reverse micellar solution (SRMS)-based solid lipid microparticles (SLMs) using homolipids from tallow fat (Bos indicus) and evaluate its potential for enhanced delivery of gentamicin. Materials and Methods: SLMs were formulated by melt-emulsification using SRMS (15% w/w Phospholipon® 90G in 35% w/w Bos indicus), polyethylene glycol 4000 (PEG) and gentamicin (1.0, 2.0, 3.0% w/w), and characterized with respect to size, morphology, encapsulation efficiency % and pH-dependent stability. The in vitro release of gentamicin from the SLMs was performed in phosphate buffer (pH 7.4) while bioevaluation was carried out using clinical isolates of Staphylococcus aureus and Escherichia coli. Results: Results showed that the lipid matrix accommodated gentamicin in a concentration-dependent manner, and that stable and spherical SLMs with size range of 18.62 ± 1.24-20.59 ± 1.36 µm and 21.35 ± 1.57-50.62 ± 2.37 µm respectively for unloaded and drug-loaded formulations were obtained. The in vitro drug release studies revealed that SRMS-based SLMs could better be used to control the release of gentamicin than gentamicin injection. Results of sensitivity test revealed that the SLMs time-dependently and capacity-limitedly produced greater inhibition zone diameters (IZDs) than the standards, an indication of improved bioactivity against the test organisms, with greater IZDs against S. aureus than E. coli. Overall, SLMs containing 2% w/w SRMS, 3% w/w gentamicin and PEG 4000 entrapped the highest amount of drug, achieved complete drug release and gave highest IZD against the organisms within 420 min, while plain gentamicin gave the least. Conclusion: This research has shown that SLMs based on Bos indicus and P90G is a potential carrier system for dissolution and bioactivity enhancement of gentamicin.
Keywords: Escherichia coli; solidified reverse micellar solutions; Staphylococcus aureus